Florida Wetlands: Extension Web Site - Mark Clark (EDIS, 2004)
Wetlands cover almost 30% of the state of Florida and account for just over 10% of the remaining wetland area in the lower 48 United States. Over the past 200 years Florida has lost an estimated 10 million acres of wetland, about half of the total area thought to exist in the 1780's. Some of these remaining wetlands are well known, like the Florida Everglades, while others may be small and unassuming. All play a vital role in flood protection, water quality and wildlife habitat. The Florida Wetlands Extension web site is designed to provide you with a better understanding of wetlands and wetland-related issues in Florida where these ecosystems are such a prominent feature. This document outlines some of the subjects covered in the site. his document is Fact Sheet SL217, one of a series of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2004.